Projek Based Learning dan Media Loose Parts dalam Melejitkan Kemampuan Literasi Steam pada Anak Usia Dini - Herna Hastuti; Rahmat Mulyono (Syntax Corporation, 2023)
The background to the problem in writing this Best Practice is because the students' ability in STEAM Literacy is very low, teachers are not varied in using approaches and learning models. The purpose of this Best Practice is to create effective, creative and imaginative learning, in introducing STEAM literacy to students and to be able to provide motivation to play naturally for children and inspire teachers to be more innovative and varied in presenting learning. Based on these problems, the teacher applies learning using a project-based learning approach to boost STEAM literacy skills and differentiate. As for the results of this Best Practice, students become more free in expressing their ideas and ideas and can solve the problems they face. Children can develop STEAM literacy skills and differentiation as well as learner-centered learning. By applying Loose Parts media, it is hoped that children will be more creative, imaginative, collaborative in accordance with the characteristics of children, that the child's world is play by playing will gain knowledge and skills and attitudes in everyday life. this it is hoped that it will form a future generation that is tough, competent, with Pancasila personality ready to face challenges in the era of globalization.